The major issues facing staff in Islamic banking industry and its impact on productivity - Harith Yas; Abbas Mardani; Ali Alfarttoosi (Contemporary Economics, 2020)
The main concern of the research were the challenges faced by the staff working in the Islamic banking Industry. The study was conducted on Islam based banks between the 5th and 22nd of March 2020 to identify the challenges faced by the staff. Again, the results obtained aided in ascertaining the correlation between the staff challenges and its unique model of operation from conventional banks. Research objectives included generating results that assisted in developing staff skills. Additionally, investigating the nature and increase in sales and implementing methods of attracting customers to the banks were the last objectives of the study. In the methodological part, the quantitative data collection focused on questionnaires, whereas qualitative concentrated on interviews with the aid of descriptive statistics and observation. The sample used was composed of 200 participants. A total number of 8 Islamic banks were engaged in retrieving the necessary information from staff. The findings acquired through the SEM approach confirm that misdemeanor and personal problems have shown their negatively insignificant impact on the productivity of the employees. Whereas, financial rewards contributed to the positive and significant impact on the productivity factor. Banking sector management, specifically in Islamic banks, would greatly benefit from acquainting themselves with the current study's findings to increase the productivity of their employees. However, significant attention is required to control the adverse influence from the miscellaneous factors, and personal problem which are causing lower employee productivity.
Keywords: M10; M14; M40; 330; employee's productivity; financial reward; job content; skills; banking industry